Planned To Be Reclaimed:: Public Design Strategies for Spontaneous Practices of Spatial Appropriation - Leveratto, Jacopo (Street Art & Urban Creativity, 2015)
Several contemporary studies on public space focus on its loss, in relation to an increase in people’s disengagement fromthese types of spaces. Since the 1960s, a considerable part of urban culture has attempted to develop strategies for peopleto re-appropriate public space and to ‘inhabit the city again.’ This has defined a line of research that, although now consolidated,is still little known in its complexity. In the effort to create a unified framework for the different attempts through whicharchitecture has historically responded to the rise of spontaneous forms of urban creativity, this paper outlines a short historyof design strategies aimed at enabling and encouraging different forms of spatial appropriation. It also highlights a gradualshift from prescriptive and repeatable rules to site-specific approaches, prompting a new disciplinary convergence betweenurban planning and design, interior architecture, industrial design and public art.